The Impact of Excellent Service and Security Management on Public Interest in Visiting Local Government Offices in the East Bekasi Region, Bekasi City - Andrian Andrian; Pratiwi Nila Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of providing good service and security on public visits to local government offices in the East Bekasi District area of Bekasi City. The research methodology used is quantitative with a purposive sampling survey method on respondents who have minimum criteria for visiting more than once and have experienced public services at local government offices. The questionnaire was distributed to 115 respondents and returned by 100 people. Then after collecting the necessary data, the data was processed by researchers using statistical analysis using SPSS version 22 of the data obtained in the field. The results showed that providing good service and security can have a significant direct impact on public interest in visiting local government offices without worry.